(3GdefGaY GdHjfI heG jUdM aj GdCQHYI GdCRefIs - (3eMeO Hf Ydj Hf YHO GdQMef Hf CMeO Hf YHO Gddg, Hfejjf GdUfgGLjs
(3ChdgG (B:s
(3jbhd (B:(3aGSJNQJ Gddg JYGdi ai LejY cJGH ai GdWH CJMa Hg Yei CHG Ydi GdMSf Hf jMji GdUfgGLi aLeYJ ef cJH YOjOI hCMGOjK eSQhOI s
(3BNQgG (B:s
(3eHJhQ hBNQ GdehLhO efg (B: (3hbGd GHf ESMGb (B:(3YPG Ydb Sf GdKYdH Ydi GdCPf GdhLjYI Scf hLYgG GdSf GdCjef hGdCjSQ Ydi GdCjSQ bGd CHbQGW EPG Ydb dHf GdCJGf s
(3ai eLdI eYgO GdeNWhWGJ (B5/290 : (3GdefGaY GdHjfI heG jfaY ai GdCRefI dLGdjfhSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B252 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs